Uma bússola visual para orientação de robôs móveis autônomos baseada em visão computacional - Nicorena, Leonardo de Oliveira (2016)
This paper presents an approach for the orientation of a autonomous humanoid robot, based on information from computer vision. The method proposed is a visual compass, which combines image processing techniques and data analysis, in order to estimate the orientation in a accurately and effective way. The visual compass consists of a circular data model in which visual features are processed and extracted from the environment, stored and then compared with new readings of the environment in order to infer the orientation of the robot.